Development And Utilization Of Aerobic Granules For Treating Low Strength Domestic Wastewater - Peyong , Yet Nee (2012)

(untitled)
Aerobic granules were developed using low strength wastewater in sequencing batch reactor (SBR). The changes in microbial morphologies and structures of aerobic granules under different organic loading rates (OLR) and their tolerance towards free ammonia (FA) and free nitrous acid (FNA) were studied. The development of aerobic granules was carried out in 3 stages. In the first stage, aerobic granules were cultivated using low strength synthetic domestic wastewater with OLR of 1.2kg/m3day. Stable aerobic granules were formed after 60 days operation with an average granule size of 2.2 mm.